ENERGY FACTOR IN THE FOREIGN POLICY OF AZERBAIJAN - E. T. Mekhdiev (Проблемы постсоветского пространства, 2017)
This article focuses on the role of the energy factor in the formation of foreign policy of the Republic of Azerbaijan. The author conducted a brief analysis of the basic directions of Azerbaijan's oil and gas strategy, which play an important role for the energy security of the European Union. As noted in the article on the increase in competition between countries for influence and access to hydrocarbon reserves in the Caspian region.